ANALISIS PEMBEBANAN LALU LINTAS PADAPERENCANAAN JALAN-JALAN PERINTIS - I Wayan Suweda (JURNAL SPEKTRAN, 2018)
Nusa Penida (20,284 ha) is nearly 2x the areas of the other three districts of Klungkung regency,which located in the Bali mainland (11,216 ha). However, the condition of people is very underdeveloped. The regionsdisparityis caused by various factor, one of them is "isolated" area of ??Nusa Penida. So,itsneed to be planned a pioneering road to improve accessibility. In the prediction of traffic assignment, of course, can not be based solely on the existing very small trip generation. For that ananalogous method should be set up to the region that has the same characteristics. Analogy method was developed through a comparative study to other areas of Bali with a similar limestone structure, the same road networkand tourist areas. In accordance with development plan, it can be predicted that the road ADT in 2020 will be 5,800.62 pcu/day and DHV725.08 pcu/hour. Meanwhile, the end of the road horizon-year 2045 reaches 37,576.31 pcu/day with DHV of 4,697.05 pcu/hour. Assuming that of the rural environment, the capacity of the 2/2UD hilly road is 2,910 pcu/hour. Therefore, from the loading analysis shows that in the year of 2038 the road should be widened to be 4 lanes to serve the-2traffic directions. Keywords:pioneer road, analogy method, nusa penida